DAKWAH BI AL-HAL AGH. SANUSI BACO IN BUILDING SOCIAL INTERACTION WITH THE COMMUNITY - Suhardi, Suhardi (TOPLAMA, 2024)
Islamic da'wah to society does not only carry out scientific orations verbally with fiery preaching rhetoric on the pulpit but also requires the example of a preacher so that the preaching delivered by the preacher can be more effective. This research is qualitative research, namely, the researcher examines the figure of a charismatic cleric in carrying out his preaching activities to the community, and the perception of the wider community regarding the example of this preacher as applied in the social life of the community. The research methods used are observation, interviews, and documentation. The results of this study indicate that AGH. Sanusi Baco is a figure of cleric as well as a preacher, who not only conveys a lot of preaching bi al-listen, but he is also known as a figure of preacher who can be used as a mirror for other preachers and other communities, or apply the concept of da'wah bi al-hal. Among other things, he is known as a preacher who is sincere, patient, trustworthy, honest, warm, and humble. Every conversation he has is full of wisdom, and it is very refreshing to communicate with him.